2010
DOI: 10.1200/jco.2009.21.8073
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Stem-Cell Transplantation for Patients 50 Years or Older With Myelodysplastic Syndromes or Secondary Acute Myeloid Leukemia

Abstract: Allogeneic hematopoietic stem-cell transplantation remains a potential curative therapeutic option for many older patients with MDS. In this analysis, disease stage at time of transplantation, but not recipient age or the intensity of the conditioning regimens, was the most important factor influencing outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
182
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(202 citation statements)
references
References 31 publications
14
182
5
1
Order By: Relevance
“…In the multivariable Cox model, the only factor that was statistically significant was diseaserisk stratification for OS, EFS and cumulative incidence of relapse. Overall, these results are very similar to the report by Lim et al 27 in patients of 50 years or older; where the disease stage at transplantation was the main independent factor predicting poor 4-year OS, HR, 1.55 (95% CI: 1.32-1.83).…”
Section: Discussionsupporting
confidence: 81%
“…In the multivariable Cox model, the only factor that was statistically significant was diseaserisk stratification for OS, EFS and cumulative incidence of relapse. Overall, these results are very similar to the report by Lim et al 27 in patients of 50 years or older; where the disease stage at transplantation was the main independent factor predicting poor 4-year OS, HR, 1.55 (95% CI: 1.32-1.83).…”
Section: Discussionsupporting
confidence: 81%
“…20 Another study of the EBMT group including 1333 patients between 50 and 74 years again shows that older age had no significant influence on the outcome. 21 Data of the CIBMTR in 1080 patients older than 40 years demonstrated in multivariate analysis that chronological age did not influence NRM, relapse or rate of GVHD, and therefore lead to the conclusion that age alone should not be a contraindication for allogeneic HCT. 22 In a recent published study of Brunner et al 13 describing patients over the age of 70 years, a 2-year-OS of 39% was found with a median follow-up of 21 months of patients alive.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 The selection of conditioning regimen (myeloablative, reduced intensity or nonmyeloablative) on the basis of age cutoffs alone is, however, not thought to be optimal when predicting NRM and survival. 13,14 Other factors, such as disease status and co-morbidities, may also affect NRM and survival and hence may need to be taken into account. 13 A number of risk-assessment scores have been utilized to predict NRM and outcomes of HCT.…”
Section: Introductionmentioning
confidence: 99%